Artificial intelligence in drug discovery - Brown, Nathan (RSC drug discovery series., 2021)
Artificial Intelligence in Drug Discovery aims to introduce the reader to AI and machine learning tools and techniques, and to outline specific challenges including designing new molecular structures, synthesis planning and simulation.